The levels of monoamine neurotransmitters and measures of mental and emotional health in HCV patients treated with ledipasvir (LDV) and sofosbuvir (SOF) with or without ribavirin (RBV). Issue 46 (November 2016) - Golabi, Pegah; Elsheikh, Elzafir; Karrar, Azza; Estep, James M.; Younossi, Issah; Stepanova, Maria; Gerber, Lynn; Younossi, Zobair M.
Abstract : Abstract: Mental and emotional health (MEH) impairment is commonly encountered in hepatitis C patients. Although the exact mechanism remains unknown, alterations in neurotransmitter and cytokine levels maybe associated with hepatitis C virus (HCV)-related MEH issues. The aim of the study was to assess association of serum biomarkers with self-reports of MEH in HCV patients before treatment and after achieving sustained virologic response (SVR). The HCV genotype-1-infected patients who achieved SVR at 12 weeks after treatment with ledipasvir (LDV)/sofosbuvir (SOF) ± ribavirin (RBV) were selected. Frozen serum samples from baseline, end of treatment (EOT), and posttreatment week 4 (PTW4) were used to assay 16 cytokines and monoamine neurotransmitters. Validated self-reports were used to assess MEH. Hundred patients were evaluated. Mean age was 53 years (57% male, 86% white). Compared with baseline, emotional well-being and emotional health significantly increased by EOT, and role emotional, emotional well-being, and emotional health significantly increased at PTW4 in the RBV-containing arm ( P  < 0.05). In patients taking LDV/SOF + RBV, serotonin levels were significantly decreased at PTW4 compared with baseline ( P  = 0.046). Compared with baseline, there were significant decreases in interleukin (IL)-10 levels at EOT and PTW4 in both treatment groups. The changes in IL-8 also differed significantly between LDV/SOF + RBV and LDV/SOF groups ( P  < 0.05). Changes in dopamine and tryptophan levels at EOT correlated with increasing emotional health scores, whereas changes in monocyte chemoattractant protein-1 at EOT and IL-8 at PTW4 correlated with increasing mental health scores. The neurotransmitters and cytokines were found to be independent predictors of MEH scores in multiple regression analysis. Cytokine and neurotransmitter changes are associated with mental and emotional health. Patient-reported outcome scores change during and after treatment. Abstract : Supplemental Digital Content is available in the text